EXPLORATION AND SCREENING OF OXYGEN REDUCING POTENTIAL IN CYTOPLASMIC MEMBRANE FRAGMENTS OF ESCHERICHIA COLI AND SALMONELLA SP. - M. U. Ahmad1; H. Qamar; Y. Anwar; M. M. Javed; M. E. Babar; Ikram-ul-Haq (Journal of Animal and Plant Sciences, 2017)
Partially purified cytoplasmic membrane fragments derived from 24 hours old cultures of poultry isolates of Escherichia coli and Salmonella sp. were screened for presence of active oxyrase. At 37°C and pH 7.5, membrane fragments of Escherichia coli and Salmonella sp. reduced 40% and 35% dissolved oxygen respectively in presence of 10mM lactate after 20 minutes. This oxygen reducing ability of each bacterial fragment is due to the active oxyrase present and its ability to dissipate oxygen was increased to 45% for Escherichia coli and 48% for Salmonella sp. at pH 8.5. After further characterization, maximum activity of 1.62U/ml of oxyrase (that depleted 65% dissolved oxygen) for Escherichia coli and 1.42U/ml (that depleted 57% dissolved oxygen) for Salmonella sp. was observed at 57°C, pH 8.5 after 20 minutes.
Keywords: Oxyrase; Methylene blue; Plasmoptysis; Dissolved-oxygen probe